Identification of novel mobile colistin resistance gene mcr-10 - Chengcheng Wang; Yu Feng; Lina Liu; Li Wei; Mei Kang; Zhiyong Zong (Emerging Microbes and Infections)
Mobile colistin resistance (mcr) genes represent an emerging challenge. Here we describe a novel mcr gene, mcr-10, on an IncFIA plasmid of an Enterobacter roggenkampii clinical strain. mcr-10 has the highest nucleotide identity (79.69%) with mcr-9 and encodes MCR-10 with 82.93% amino acids identical to MCR-9. mcr-10 confers 4-fold increase in colistin MIC (from 1 to 4 mg/L) when cloned into a colistin-susceptible E. roggenkampii strain. By screening GenBank, mcr-10 was found in various Enterobacteriaceae species of countries in four continents, suggesting that this gene has widely spread. MCR-10 shows 79.04% to 83.67% amino acid identity and highly conserved predicted protein structures with chromosomally encoded MCR-like phosphoethanolamine transferases (designated MCR-B here) of various Buttiauxella species. MCR-10, MCR-9 and MCR-B proteins may, therefore, originate from a common ancestor. mcr-10 was adjacent to a site-specific recombinase-encoding gene and was bracketed by IS903 and may be mobilized by site-specific recombination or composite transposon. Our results indicate that mcr-10 is a novel plasmid-borne colistin resistance gene and warrants immediate monitoring and further studies.